Desirable Characteristics of Graduates in Jazz Study based on Thai Qualifications Framework for Higher Education - รักตประจิต ศักดิ์ระพี; สทุธจิต ณรุทธ์ (Journal of Roi Et Rajabhat University, 2016)
This qualitative study aimed to study the desirable characteristics of undergraduate students majoring in jazz study. Thirty-nine participants were selected through purposive sampling: 1) two jazz study experts, 2) eight jazz study lecturers, 3) twenty-two students in year 1-4 of jazz study programs, 4) five jazz study graduates, and 5) two employers of jazz study graduates. The research instruments were five sets of interview form with open-ended questions. All questions were checked by three experts for content validity. The Item-Objective Congruence Index (IOC) ranged from 0.79-0.96. Data were collected from April to June in 2016. Content analysis and methodological triangulation were used to describe the data. Results indicated that the desirable characteristics of graduates in jazz study consisted of six characteristics: 1) ethics and morality, 2) knowledge, 3) cognitive skills, 4) interpersonal skills and responsibility, 5) numerical analysis, communication and information technology skills, and 6) psychomotor skills. These six domains are congruent with the Thai qualifications framework for higher education. Therefore, determining the desirable characteristics of jazz study graduates should consider the qualifications framework as a principle for curriculum development, teaching and learning processes, and learning outcome evaluation in order to produce high-quality